PREDICTION ANALYSIS OF BANKRUPTCY USING THE ZMIJEWSKI MODEL ON CONSTRUCTION SUBSECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Ilfa Hanafi; Anwar, Muh. Ilham Wardhana Haeruddin, Siti Hasbiah, Muh Ichwan Musa (Adisam Publisher, 2024)
This research aims to analyze bankruptcy predictions for construction sub-sector companies listed on the Indonesia Stock Exchange using the Zmijewski model. This research uses secondary data in the form of financial statements and closing stock prices of each company for the period 2017-2021. The sampling was conducted using purposive sampling techniques, and 15 companies that met the predetermined criteria were obtained. The research results indicate that out of 15 companies, PT Acset Indonusa Tbk, PT Adhi Karya (Persero) Tbk, and PT Waskita Karya (Persero) Tbk are predicted to be at risk of bankruptcy. The calculation results of stock returns indicate that the decrease and increase in stock returns do not correlate with the predicted bankruptcy outcomes of the company.